1994
DOI: 10.1212/wnl.44.8.1427
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological prediction of dementia and the absence of dementia in healthy elderly persons

Abstract: Identification of elderly individuals with low and high risk for future dementia has emerged as an important clinical and public health issue. To address this issue, we assessed neuropsychological performance in 317 initially nondemented elderly persons between 75 and 85 years of age and followed them for at least 4 years as part of the Bronx Aging Study. Four measures of cognitive function from the baseline assessment (delayed recall from the Buschke Selective Reminding Test, recall from the Fuld Object Memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
263
4
11

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(294 citation statements)
references
References 0 publications
15
263
4
11
Order By: Relevance
“…Numerous studies have now shown that subtle cognitive changes can precede the diagnosis of AD by a few years or more (Bäckman et al, 2001;Bondi et al, 1994Bondi et al, , 1995Bondi et al, , 1999Chen et al, 2001;Lange et al, 2002;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998;Small et al, 1998Small et al, , 2000Smith et al, 1998). As Sliwinski and colleagues (1996) have shown, the inclusion of such individuals with preclinical AD in a normative sample leads to an underestimate of the mean, an overestimate of the variance, and an overestimate of the effect of age on a given cognitive measure, all of which reduces the sensitivity of the measure for detecting mild impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have now shown that subtle cognitive changes can precede the diagnosis of AD by a few years or more (Bäckman et al, 2001;Bondi et al, 1994Bondi et al, , 1995Bondi et al, , 1999Chen et al, 2001;Lange et al, 2002;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998;Small et al, 1998Small et al, , 2000Smith et al, 1998). As Sliwinski and colleagues (1996) have shown, the inclusion of such individuals with preclinical AD in a normative sample leads to an underestimate of the mean, an overestimate of the variance, and an overestimate of the effect of age on a given cognitive measure, all of which reduces the sensitivity of the measure for detecting mild impairment.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of these individuals meeting criteria for amnestic Mild Cognitive Impairment (aMCI) develop AD at elevated rates and have become the targets of secondary prevention trials (Petersen et al, 2005). The definition of MCI has been broadened to include clinical subgroups that have other cognitive deficits including impaired attention or executive dysfunction, (Albert et al, 2001;Masur et al, 1994;Saxton et al, 2004;Tierney et al, 2005), language (Jacobs et al, 1995), or visual spatial impairment (Small et al, 1997). Conversion rates to dementia vary because of differences in cohorts, MCI criteria, and the methods used to implement them.…”
Section: Introductionmentioning
confidence: 99%
“…In most longitudinal studies, memory measures are better predictors of subsequent AD than executive function tests (Devanand et al, 1997;Elias et al, 2000;Linn et al, 1995;Masur et al, 1994;Rubin et al, 1998) though this point is somewhat controversial (Chen et al, 2001;Fabrigoule et al, 1998;Rapp & Reischies, 2005;Royall et al, 2004). In these prospective studies, cognitive scores at the time of a baseline assessment are used to predict the onset of dementia at future times.…”
Section: Introductionmentioning
confidence: 99%
“…One area of cognition that has shown promise as a preclinical marker of AD in elderly individuals with the ApoE-e4 allele is attention and working memory. Specifically, some studies have found that nondemented elderly with the e4 genotype show subtle deficits on neuropsychological tests that have strong attentional demands, such as the Digit Span subtest (Albert, Moss, Tanzi, & Jones, 2001;Caselli et al, 1999;Caselli et al, 2001;Linn et al, 1995;Wilson et al, 2002); WMS-R Mental Control subtest (Tierney et al, 1996), Operation Span Test (Rosen, Bergeson, Putnam, Harwell, & Sunderland, 2002), Digit Symbol subtest (Masur, Sliwinski, Lipton, Blau, et al, 1994;Yaffe, Cauley, Sands, & Browner, 1997), attentional switching and disengagement (Greenwood, Sunderland, Friz, & Parasuraman, 2000;Parasuraman, Greenwood, & Sunderland, 2002), and supra-span ability and divided attention (Rosen et al, 2002). However, several other studies have failed to replicate findings of attentional deficits in nondemented e4 elderly groups (Baeckman, Small, & Fratiglioni, 2001;Elias et al, 2000;Flory, Manuck, Ferrell, Ryan, & Muldoon, 2000;Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%